Effect of Eyelid Margin Cleaning on Conjunctival and Eyelid Bacterial Flora Before Intraocular Surgery. (18th August 2018) - Thanathanee, Onsiri; Pulnitiporn, Rawipaparas; Anutarapongpan, Orapin; Suwan-Apichon, Olan; Bhoomibunchoo, Chavakij
ABSTRACT: Purpose : To compare the bacterial cultures of the lower eyelid margins and lower fornices between ocular irrigations with and without eyelid margin cleaning before intraocular surgery. Methods : A prospective study was carried out that included 102 eyes from 51 patients undergoing intraocular surgery between December 2016 and April 2017. In each patient, the surgical eye (control group) only received ocular irrigation and the opposite eye (study group) received ocular irrigation with eyelid margin cleaning. Normal saline solution was used in all procedures. In each group, samples from the lower eyelid margins and lower fornices were cultured before and after cleaning. Povidone iodine and antibiotic eye drops were instilled after specimen collection. Results : The most common bacterial isolate of all groups was Staphylococcus spp . There were no statistically significant differences of positive cultures between the control and study groups in either lower eyelid margins(Odds ratio [OR], 2.19; 95% CI, 0.84–5.72) nor lower fornices(OR, 0.93; 95% CI, 0.43–2.00) . In addition, there were no statistically significant differences of positive cultures between before and after eyelid cleanings from both lower eyelid margins(OR, 2.74; 95% CI, 0.53–14.24) and lower fornices(OR, 0.73; 95% CI, 0.21–2.57). Conclusions : Eyelid margin cleaning with normal saline solution immediately before intraocular surgery did not help to decrease microbial loading on the ocular surfaces. The rate of bacterial contamination, however, was not increased which could be due to not performing eyelid compression.